Azobenzene-based inhibitors of human carbonic anhydrase II - Runtsch, Leander Simon; Barber, David Michael; Mayer, Peter; Groll, Michael; Trauner, Dirk; Broichhagen, Johannes (Beilstein Journal of Organic Chemistry, 2015)
Aryl sulfonamides are a widely used drug class for the inhibition of carbonic anhydrases. In the context of our program of photochromic pharmacophores we were interested in the exploration of azobenzene-containing sulfonamides to block the catalytic activity of human carbonic anhydrase II (hCAII). Herein, we report the synthesis and in vitro evaluation of a small library of nine photochromic sulfonamides towards hCAII. All molecules are azobenzene-4-sulfonamides, which are substituted by different functional groups in the 4´-position and were characterized by X-ray crystallography. We aimed to investigate the influence of electron-donating or electron-withdrawing substituents on the inhibitory constant Ki. With the aid of an hCAII crystal structure bound to one of the synthesized azobenzenes, we found that the electronic structure does not strongly affect inhibition. Taken together, all compounds are strong blockers of hCAII with Ki = 25–65 nM that are potentially photochromic and thus combine studies from chemical synthesis, crystallography and enzyme kinetics.
Keywords: azobenzene chemistry; enzyme inhibitors; human carbonic anhydrase II; sulfonamide; X-ray crystallography